A Comprehensive Exploration of Global Trends Impacting Financial Sustainability in the Middle East (Saudi Arabia) - Alenezi, Marim (Journal of Ecohumanism, 2025)
The main topic of this study is how the economies of the world and the Middle East are connected and impact each other. We use old data to look at how changes in world events, trade patterns, and foreign economic policy affect the economy here. If countries in the Middle East want to grow and expand their businesses, they need to pay attention to outside forces that have an impact on their money. This article’s author carefully looks at statistics from the past, the present, and the future to show how money problems in the Middle East are linked to changes in the world economy. Recent events in geopolitics have an effect on investor trust, the security of the regional economy, and the long-term financial health of the area. This part will compare events from the past and the present to find trends that show how the area has affected the world over time. If you want to learn more about how trade trends affect countries in the Middle East, read this in-depth study. We use secondary sources to look at how customer tastes, new markets, and trade deals have changed the economies of the Middle East. Because trade around the world is always changing, these countries respect variety and being able to change. We want to know how money moves made in other countries have affected the Middle East’s funds. That’s what this study is all about. This research is mostly about how global banks, changes in the government, and group projects impact the US economy. Other sources can help us understand how governments in the Middle East have changed their economic policies, rules, and laws in response to outside forces and changes in global economic trends. This kind of research shows how changes in foreign banking affect the Middle East’s ability to keep its money in the bank. Many outside sources are used in the study to see how well the area can handle and adjust to changes from outside. It’s a great way for people who care about the Middle East’s business, economists, and leaders to find out how things are going